Prevalence, Appropriateness, and Outcomes of Colistin Use in Multidrug-Resistant Pseudomonas aeruginosa Infections: Insights from Hospital Data - Rana K. Abu-Farha; Savana Sobh; Khawla Abu Hammour; Feras Darwish El-Hajji; Sireen A. Shilbayeh; Rania Itani (Medicina)
Background and Objectives: This study aimed to assess the prevalence of colistin prescriptions among patients with multidrug-resistant (MDR) Pseudomonas aeruginosa (P. aeruginosa) infections admitted to a tertiary teaching hospital in Jordan. Additionally, the study evaluated the appropriateness of colistin prescriptions and assessed resistance levels of this strain. Materials and Methods: In this retrospective study, adult patients who were infected with MDR P. aeruginosa and were admitted to Jordan University Hospital between January 2018 and March 2024 were included. Data on demographics, clinical characteristics, sources of infection, antibiotic therapy, and clinical outcomes were collected. Results: Out of the 85 patients who met the inclusion criteria for having MDR P. aeruginosa, colistin was administered to 16 patients (18.8%). Notably, approximately two-thirds (68.7%) of the isolates from patients who received colistin were classified as extensively drug-resistant (XDR). Among the isolates, 15 out of 16 (93.8%) were resistant to both ciprofloxacin and imipenem. Among the patients requiring colistin, five (31.3%) discontinued therapy, while two (12.5%) remained on colistin despite the availability of safer alternatives. No significant difference was observed in 30-day all-cause mortality between patients treated with colistin (0%) and those who were not (4.3%, p = 1.00). Similarly, the incidence of acute kidney injury did not differ significantly between the colistin group (0%) and the non-colistin group (p = 1.00). No significant difference was found in the hospital stay between colistin-treated patients (median 10.5 days, IQR [5.0–14.0]) and those not treated with colistin (median 13.0 days, IQR [7.0–21.0]), (p = 0.22). Conclusions: This study demonstrated that colistin was selectively initiated in high-risk patients, particularly those with XDR P. aeruginosa. However, its inappropriate continuation despite safer alternatives, as well as its discontinuation when no other options existed, raise concerns about antibiotic de-escalation practices. Interestingly, no significant differences in mortality or acute kidney injury were observed between patients who were treated with colistin and those who were not. These findings emphasize the need for antimicrobial stewardship programs and highlight the importance of large-scale trials to evaluate colistin’s efficacy and safety in MDR infections.